2022
DOI: 10.7554/elife.71226
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic smoothing of collective migration

Abstract: Collective migration—the directed, coordinated motion of many self-propelled agents—is a fascinating emergent behavior exhibited by active matter with functional implications for biological systems. However, how migration can persist when a population is confronted with perturbations is poorly understood. Here, we address this gap in knowledge through studies of bacteria that migrate via directed motion, or chemotaxis, in response to a self-generated nutrient gradient. We find that bacterial populations autono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 102 publications
4
46
0
Order By: Relevance
“…It was recently shown that colonies of motile E. coli in similar matrices but with larger pores—sufficiently large for cells to swim through—smooth out any perturbations to their colony morphology using directed motility, retaining flat, cylindrical surfaces [35, 36]. We observe starkly-differing behavior for the case of purely growth-driven colony expansion considered here.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…It was recently shown that colonies of motile E. coli in similar matrices but with larger pores—sufficiently large for cells to swim through—smooth out any perturbations to their colony morphology using directed motility, retaining flat, cylindrical surfaces [35, 36]. We observe starkly-differing behavior for the case of purely growth-driven colony expansion considered here.…”
Section: Resultsmentioning
confidence: 65%
“…Our experiments used five different bacterial strains: E. coli W3110 (motile) and ΔflhDC (non-motile), both of which constitutively express GFP; V. cholerae JY030 [148]; P. aeruginosa PAO 1 ΔfliC; and K. sucrofermentans ATCC-700178. In each experiment, we first prepare a dense suspension of cells in the liquid cell culture medium used to swell the granular hydrogel matrix, and then use this suspension as the inoculum that is 3D-printed into the matrix, following our previous work [34, 35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because our model describes spreading over large length and time scales, we expect it could help more accurately describe the spreading dynamics of bacteria in processes ranging from infections, drug delivery, agriculture, and bioremediation. To this end, it would be interesting to extend our one-dimensional simulations to higher dimensions, which could result in additional rich dynamics e.g., as recently explored in [ 73 ], and to media with spatially-varying confinement.…”
Section: Discussionmentioning
confidence: 99%
“…Other work studying E. coli in 3D environments has shown that chemotaxis enables large-scale perturbations to the overall morphology of a population to be smoothed out as cells migrate, enabling them to continue to migrate together as a coherent band 252 . This population-scale smoothing unexpectedly reflects the manner in which individual cells transduce external signals during chemotaxis.…”
Section: External Stimulimentioning
confidence: 99%